Stage 4 s neuroblastoma: features, management and outcome of 268 cases from the Italian Neuroblastoma Registry - Bruno De Bernardi; Andrea Di Cataldo; Alberto Garaventa; Paolo Massirio; Elisabetta Viscardi; Marta Giorgia Podda; Aurora Castellano; Paolo D’Angelo; Elisa Tirtei; Fraia Melchionda; Simona Vetrella; Francesco De Leonardis; et al. (Italian Journal of Pediatrics, 2019)
Abstract Background Infants diagnosed with stage 4 s neuroblastoma commonly experience spontaneous disease regression, with few succumbing without response to therapy. We analyzed a large cohort of such infants enrolled in the Italian Neuroblastoma Registry to detect changes over time in presenting features, treatment and outcome. Methods Of 3355 subjects aged 0–18 years with previously untreated neuroblastoma diagnosed between 1979 and 2013, a total of 280 infants (8.3%) had stage 4 s characteristics, 268 of whom were eligible for analyses. Three treatment eras were identified on the basis of based diagnostic and chemotherapy adopted. Group 1 patients received upfront chemotherapy; Group 2 and 3 patients underwent observation in the absence of life-threatening symptoms (LTS), except for Group 3 patients with amplified MYCN gene, who received more aggressive therapy. Results The three groups were comparable, with few exceptions. Ten-year overall survival significantly increased from 76.9 to 89.7% and was worse for male gender, age 0–29 days and presence of selected LTS on diagnosis, elevated LDH, and abnormal biologic features. Infants who underwent primary resection ± chemotherapy did significantly better. On multivariate analysis, treatment eras and the association of hepatomegaly to dyspnea were independently associated with worse outcome. Conclusions Our data confirm that stage 4 s neuroblastoma is curable in nearly 90% of cases. Hepatomegaly associated to dyspnea was the most important independent risk factor. The cure rate could be further increased through timely identification of patients at risk who might benefit from surgical techniques, such as intra-arterial chemoembolization and/or liver transplantation, which must be carried out in institutions with specific expertise.